Innovación social Y su incidencia en el desarrollo económico local del Cantón La Mana, Año 2023 - López Vera, Willy Alberto (2025)
Social innovation and its impact on local economic development in the La Mana canton faces significant challenges related to poverty and informal employment, which affect its socioeconomic development, the lack of jobs, and the poor use of natural, tourism, and water resources. These problems directly affect the region's socioeconomic development, highlighting the need for innovative strategies that foster entrepreneurship and improve working conditions. Social innovation has established itself as a key driver of socioeconomic development, addressing social issues and fostering community participation. It innovates products and services that meet social needs and generate more effective social relationships, thus driving sustainable development and fostering social inclusion by integrating the most vulnerable sectors into productive and decision-making processes. The effective implementation of social innovations can facilitate the creation of formal jobs, improve residents' quality of life, and contribute to a sustainable economy. Therefore, this study not only seeks to assess the current state of local economic development in La Maná, but also to propose solutions that should be implemented by local authorities and community actors to foster inclusive and sustainable economic development that benefits the entire population of the canton.